Sovereignty above international regime: Framework of convention on tobacco control agenda in Indonesia - Satriya Wibawa; Affabile Rifawan; Bayu Kharisma; Amaliya Amaliya (Cogent Social Sciences, 2023)
Framework of Convention for Tobacco Control is the international regime and norm that provides regulation for cigarette and tobacco industries in global level. Indonesia has its narrative in declining FCTC ratification proposal. This study attempts to describe Indonesian interest and sovereignty as part of third world country over FCTC as international regime. The method uses analytical descriptive with qualitative approach using sovereignty, international regime compliance, and national interest concept in the framework of international regime. In addition, dependency theory is also used to emphasize the relationship between Indonesia and FCTC. The main reason of Indonesian narrative against FCTC agenda is historical roots with national heritage and the tobacco industry contribution to Indonesia economy. In other words, iobacco products in Indonesia is no longer concern of health issues, but also the economy and culture. Beside that, Indonesia position is in line with sovereignty principle that apply also for US and Switzerland as the country which do not ratify FCTC in its national regulation on tobacco. The elaboration of this research is divided into two parts. The research found that the FCTC are not that harmful to the business of international cigarette company such as Phillip Morris International, it even creates a new business opportunity for them. The FCTC also believed to form a dependency relationship, where the industry of developing country such as Indonesia is dependent on the global interest which is mostly sponsored by developed country to be able to grow.